2001
DOI: 10.1046/j.1439-0272.2001.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Internal spermatic vein diameter and age at operation reflect the response to varicocelectomy

Abstract: It was evaluated whether the diameter of internal spermatic veins (measured directly during operation) correlates with the clinical grade and treatment outcome following varicocelectomy. Fifty-seven consecutive men undergoing left varicocelectomy were included in the study, and spermatic vein diameter was compared with the response to the operation. The diameter appeared larger with increasing clinical grade (subclinical: 3.40 +/- 1.64 mm; grade 1 : 2.74 +/- 0.84 mm; grade 2 : 3.70 +/- 1.09 mm; grade 3 : 4.38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The effectiveness of this surgical procedure has been confirmed in palpable or large varicocele. However, even subclinical varicocele shows remarkable postoperative improvement, and several studies have shown that the improvements in testicular histology 10 and spermiogram 11 are not related to varicocele size. In the era of ART, many urologists and andrologists consider that the purposes of varicocele treatment are to achieve patient satisfaction and cost‐effectiveness by natural pregnancy or IUI instead of IVF or ICSI.…”
Section: Role Of Sperm Factors In Icsimentioning
confidence: 99%
“…The effectiveness of this surgical procedure has been confirmed in palpable or large varicocele. However, even subclinical varicocele shows remarkable postoperative improvement, and several studies have shown that the improvements in testicular histology 10 and spermiogram 11 are not related to varicocele size. In the era of ART, many urologists and andrologists consider that the purposes of varicocele treatment are to achieve patient satisfaction and cost‐effectiveness by natural pregnancy or IUI instead of IVF or ICSI.…”
Section: Role Of Sperm Factors In Icsimentioning
confidence: 99%
“…Metin et al (1991) reported varicocele in 100% of cases with a 5–6 mm vein diameter; in 50% if 3–4 mm; and in 16% if 1–2 mm. Shiraishi et al (2001) positively correlated mean vein diameter with its grade (subclinical: 2.40 mm; grade I: 2.74 mm; grade II: 3.7 mm; grade III: 4.38 mm). Kocakoc et al.…”
Section: Discussionmentioning
confidence: 91%
“…In another study, patients were subdivided into those <30 years and those ≥30 years to determine the effect of age on varicocelectomy results. The authors indicated that patient age at the time of the operation was of greater value for predicting the treatment outcome of a varicocelectomy [25]. In contrast to that report, the reproductive outcomes of infertile couples with a clinical varicocele and advanced paternal age were evaluated by Zini et al [26].…”
Section: Discussionmentioning
confidence: 98%